The Family Ambitions of Sigismund Attems Petzenstein in the Light of his Art Commissions - Quinzi, Alessandro (Acta historiae artis Slovenica, 2021)
In the mid-18th Century Count Sigismund Attems Petzenstein (1708–1758) “raised his family to such greatness as it had not attained in all past times” (G. Guelmi, Storia genealogico-cronologica degli Attems austriaci, 1783). He cemented the newly acquired reputation with the erection of a town residence in Corno Square (1745), a villa in Podgora (Piedimonte, 1747–1748) and the renovation of the mansion at Jazbine (Giasbana, 1747), all in Gorizia. In 1750, when his brother Karl Michael (1711–1774) was appointed the first archbishop of Gorizia, he had the façade of the town palace modernized. As a rule, Sigismund used the architect Saverio Gianni to execute the works, as is evidenced by data from the estate inventory now published for the first time. He commissioned paintings from the Gorizian painters Johann Michael Lichtenreit and Antonio Paroli, whereas for the altar painting of the family chapel in the former church of St Francis he turned to the Veronese artist Giambettino Cignaroli. Although Sigismund did not live to see the painting hung, it was by means of this artistic commission that he joined the elite circle of Cignaroli’s European clients.